eCM 2013
DOI: 10.22203/ecm.v026a13
|View full text |Cite
|
Sign up to set email alerts
|

Solid freeform-fabricated scaffolds designed to carry multicellular mesenchymal stem cell spheroids for cartilage regeneration

Abstract: Three-dimensional (3D) cellular spheroids have recently emerged as a new trend to replace suspended single cells in modern cell-based therapies because of their greater regeneration capacities in vitro. They may lose the 3D structure during a change of microenvironment, which poses challenges to their translation in vivo. Besides, the conventional microporous scaffolds may have difficulty in accommodating these relatively large spheroids. Here we revealed a novel design of microenvironment for delivering and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In previous literature, it was found that proliferation, differentiation, and migration potential of MSCs were raised when MSCs were cultured as spheroids. 16,37 In addition, the formation of MSC spheroids could increase cytokine release and thus possibly enhance the paracrine effect, 15,40 which was important for MSCs on wound healing as previously described. Previous studies also suggested that preservation of MSCs as spheroids was essential for beneficial properties of MSC spheroids.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In previous literature, it was found that proliferation, differentiation, and migration potential of MSCs were raised when MSCs were cultured as spheroids. 16,37 In addition, the formation of MSC spheroids could increase cytokine release and thus possibly enhance the paracrine effect, 15,40 which was important for MSCs on wound healing as previously described. Previous studies also suggested that preservation of MSCs as spheroids was essential for beneficial properties of MSC spheroids.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies also suggested that preservation of MSCs as spheroids was essential for beneficial properties of MSC spheroids. It was demonstrated that embedding spheroids in HA gel loaded in a chitosan‐grafted scaffold assisted to maintain spheroid morphology . These were the reasons why we made an attempt to utilize MSC spheroids rather than single cells in HA gel combined with the chitosan membrane for wound healing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of tissue spheroids occurs, however, only if they are held in direct contact with each other. To hold tissue spheroids next to each other at a predetermined position in a 3D space, 3D printed synthetic scaffolds [4,5], dif ferent hydrogels [6], and even metal rods [7] are used, with varying degrees of effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to enable post-printed tissue spheroids fusion it 3 is necessary to keep them close to each other in threedimensional space. Several different approaches have been developed to enable controllable tissue spheroids fusion, which include placing tissue sphe-roids inside 3D printed synthetic scaffolds [11][12][13] , using bioprintable hydrogel [14,15] and even metallic rods [16] . The search for the effective methods to keep tissue spheroids close to each other during 3D bioprinting continues and one of the possible perspective approaches is an application of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%